The Influence of Total Quality Management To Profit in the MSME Culinary Sector - Maulanisha Ihsani Gendroyono; Mohamad Hasanuddin; Maria Th. Heni Widyarti (Applied Accounting and Management Review (AAMAR), 2022)
Destination from study this is for analyze the effect of total quality management (TQM) on profits moderated by the performance of MSMEs after the COVID-19 pandemic. Study This research was carried out on SMEs in the fast food culinary sector in the Mranggen district of Demak. Variable free from study this is total quality management and performance, variable dependent is profit and there one variable moderation that is performance. Indicator of the total quality management used in study this is customer focus, improvement _ sustainability, and empowerment employees. Respondents used _ as any as 60 senior employees at selected MSMEs use purposive sampling technique. Method data collection that is method survey with use questionnaire. Study this using a data quality test consisting of from the validity test and reliability test, continued with using assumption test classic consisting of from normality test, heteroscedasticity test and multicollinearity test then test the hypothesis which consists of from Moderated Regression Analysis (MRA), t test (partial) and f test (simultaneous) and coefficient test determinant (R 2). Research results state that total quality management variable has an effect significant and positive (97.113 > 2.54) towards profit by partial, and variable MSME performance has an effect significant and positive (3.713 > 2.120) towards profit by partial. MSME performance variable is not succeed moderate (0.867) the effect of total quality management on earnings.